(untitled) (International Journal of Physiotherapy, 2016)
Background: Low back pain (LBP) is one of the major and commonest musculoskeletal disorders among all age groups with substantial challenges for clinical management. The psychological overlay can be detected only in chronicity of the condition. Current research highlights sub grouping LBP is a priority for target specific treatments.Hence the aim of the study was to categorize subjects into three subgroups of risk using STarT Back Screening tool. Methods: An observational-follow up study was conducted with subjects of sample size 40 (aged 18 to 65) having low back pain of duration less than one month. The principle investigator administered the screening tool to the subjects. The self- administered Tamil version of 9 items STarT back screening tool was administered. Based on the risk level, counseling was imparted and re analysis of values were done a month later using the same tool. Results: The mean pre total score is 4.48±1.8 and post total score after a month is 2.03±1.18.The mean pre sub score is 2.28±1.21 and post total sub score after a month is 1.18±0.84.On comparing the pre and post scores, it was found to be statistically highly significant(p-.0005) in total and sub scores. Conclusion: The study concludes that STarT back screening tool is an easy, simple tool in sub grouping acute low back pain. The tool proved to be efficient in predicting risk in acute low back pain in a short duration of follow up.